India Desperately Needs Research Based, Innovative World Class Institutes - Naik, B. M. (Journal of Engineering Education Transformations, 2011)
The paper presents in brief, need and importance of research based innovative world class universities and colleges, for global competitiveness. To win in a competitive world, India needs professionals of world class standard, which with higher imagination can make India forerunner. Graduates to become Pace setters, technology pioneers and industry leaders demand institutes to be ahead of time. Conventional institutes produce mediocre, followers, fit to become soldiers at best in multinationals. There is huge energy in Indian youths, yet too few become leaders in industry and technology on global plane, because that is not what present institutes are teaching students to become. If we do not envision building research based world class institutes, we will lose in brain race; India will continue to trail behind the developed world. Students demand world class education. They are ready to pay for it. But not many are able to offer. Thousands of students every year go abroad. Foreign universities are coming. World class institutes are innovative in character. They generate Jobs, entrepreneurs and high income. In knowledge driven economy of today, they assume high significance. Industry looks at these institutes as "Light Houses". They are an idea source. They energize national and international environment. Spending any amount to make institutes world class is Justifiable. Can India hope to be a developed nation with present poor quality higher&technical education? At least some better performing institutions should forthwith be enabled to reach to world class status. Can we create world class centers of excellence? This will decide India s future. The number of world class institutes is now a differentiating factor between more developed and less developed countries. The paper identifies strategies which contribute to make an institution world class. The strategies are grouped as governance, academic, administrative, financial etc. They are, however, tough to deliver and essentially call for political will.